Loyalty of the organization’s personnel: approaches to defining - Бутиліна, О. В. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2017)
The article is devoted to the analysis of phenomenon of loyalty of the organization’s personnel. The author uses the theory of exchange and expectations theory to determine the essence and components of staff loyalty. The emotional, rational and behavioral components are considered. Loyalty is a social characteristic of the organization. This allowed to explain some models of staff loyalty.